PRESENCE OF PTYCHODUS MORTINI (ELASMOBRANCHII: PTYCHODONTIDAE) IN THE UPPER CRETACEOUS OF VENEZUELA - Carrillo-Briceño, Jorge D. (2011)
Ptychodus mortoni is a durophagous shark characteristic from the Upper Cretaceous, with a chronostratigraphic record between the Turonian-Maastrichtian. The present contribution illustrates and describes a set of teeth of Ptychodus mortoni from the La Luna Formation, Upper Cretaceous of the Sierra de Perijá, Zulia State, Venezuela. This material represents the only known record for South America, increasing the paleobiogeographi distribution of the taxon, which was previously known only from Africa, North America and Europe.